Fluidic Elements based on Coanda Effect - Constantin OLIVOTTO (INCAS Bulletin, 2010)
This paper contains first some definitions and classifications regarding the fluidic elements. Thegeneral current status is presented, nominating the main specific elements based on the Coanda effect developedspecially in Romania. In particularly the development of an original bistable element using industrial compressedair at industrial pressure supply is presented. The function of this element is based on the controlled attachmentof the main jet at a curved wall through the Coanda effect. The methods used for particular calculation andexperiments are nominated. The main application of these elements was to develop a specific execution element:a fluidic step–by-step motor based on the Coanda effect.